Non-fullerene receptor with spatial confinement crystallization characteristic and preparation method and application thereof
By introducing asymmetric oligoethylene glycol chains into non-fullerene receptors, regulating their molecular assembly, and developing receptors with spatially limited crystallization properties, solving the thickness of non-fullerene receptors in the prior art The problem of low performance in the film achieves efficient and stable performance of organic solar cells.
Patent Information
- Application Number
- CN202411639557.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-16
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2044-11-16
AI Technical Summary
The existing non-fullerene receptors are difficult to obtain high performance in thick films, which limits the industrialization process of organic solar cells.
Develop non-fullerene receptors with spatially confined crystallization properties, and regulate the molecular assembly process of the receptor by introducing asymmetric oligoethylene glycol chains, induce face-on orientation, enhance crystallinity and perpendicularity Phase separation.
The preparation of high-performance organic solar cells under thick film conditions is realized, which improves film thickness independence, maintains high efficiency, and improves the working stability of the device.
Smart Images

Figure CN119490513A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of photovoltaic materials, and in particular relates to the application of non-fullerene acceptors with spatially confined crystallization properties in solar cells. Background Art
[0002] Organic solar cells (OSCs) are a promising solar technology. Researchers have made great efforts in device engineering, molecular structure modification of photovoltaic materials, and optimization of active layer morphology, which have increased the photoelectric conversion efficiency (PCE) of OSCs to more than 19%. However, high-efficiency OSCs are usually obtained with an active layer thickness of about 100nm, but it is difficult to produce uniform and defect-free films in industrial high-throughput preparation. Therefore, the use of thicker active layers exceeding a few hundred nanometers can greatly expand the printing process window, which is crucial to meet the requirements of large-scale manufacturing. However, increasing the thickness of the active layer usually leads to reduced PCEs. Therefore, in order to meet the requirements of high-throughput roll-to-roll manufacturing, it is crucial to develop efficient "thick film" OSCs. Summary of the invention
[0003] To solve the above problems, the purpose of the present invention is to provide a non-fullerene acceptor with spatially confined crystallization performance and a preparation method thereof, so as to overcome the deficiency that the existing non-fullerene acceptors cannot obtain high performance in thick films, lay the foundation for their large-area preparation, and promote the industrialization process of organic solar cells.
[0004] To achieve the above technical objectives, the present invention is implemented by the following technical solutions: a non-fullerene receptor with spatially confined crystallization performance, containing an ethylene glycol group, preferably having an asymmetric oligoethylene glycol chain; its chemical structure is one of the following chemical structures:
[0005]
[0006] Wherein, X1, X2, X3, and X4 are independently selected from one of O, S, Se, and Te; D1 to D4 are independently selected from one of H, CH3, OCH3, F, Cl, Br, CF3, CN, and C a H 2a+1 One of the following, wherein a is 1 to 20;
[0007] The end groups A1 and A2 are independently selected from one of the following structural formulas:
[0008]
[0009] Wherein B1 and B2 are independently selected from or B3-B8 are independently selected from H, CH3, OCH3, F, Cl, Br, CF3, CN, Cb H 2b+1 One of the following, wherein b is 1 to 20;
[0010] R1 is -C n H 2n+1 , wherein n is 1 to 20; R2 is -(CH2CH2O) m CH3 or -C n H 2n+1 , wherein m is 1 to 10, n is 1 to 20; R3 is -(CH2CH2O) m CH3 or -C n H 2n+1 , wherein m is 1 to 10, n is 1 to 20; R4 is hydrogen, -(CH2CH2O) m CH3 or -C n H 2n+1 , wherein m is 1 to 10, n is 1 to 20; R5 is hydrogen, -(CH2CH2O) m CH3 or -C n H 2n+1 , where m is 1 to 10, n is 1 to 20;
[0011] In Formula 1, Formula 4, Formula 5, and Formula 6, R2 is different from R3; in Formula 2, R2, R3, and R4 are not completely the same; in Formula 3, R2, R3, R4, and R5 are not completely the same.
[0012] In the above technical solution, R1 is -C n H 2n+1 , wherein n is 3 to 10; R2 is -(CH2CH2O) m CH3 or -C n H 2n+1 , wherein m is 1 to 5, n is 5 to 15; R3 is -(CH2CH2O) m CH3 or -C n H 2n+1 , wherein m is 1 to 5, n is 5 to 15; R4 is hydrogen or -C n H 2n+1 , wherein n is 3 to 15; R5 is hydrogen or -C n H 2n+1 , where n is 3 to 15.
[0013] The present invention discloses a method for preparing the above-mentioned non-fullerene receptor with spatially confined crystallization, comprising the following steps: reacting a DA'D type conjugated core with an electron-withdrawing end group to obtain a non-fullerene receptor with spatially confined crystallization. Preferably, the reaction is carried out under nitrogen protection, in a solvent, and in the presence of a catalyst, and the reaction time is 10 to 30 hours, and the temperature is 50 to 80°C; the molar ratio of the DA'D type conjugated core to the electron-withdrawing end group is 1: (1 to 10) preferably 1: (2 to 6). The above-mentioned solvent is chloroform, dichloromethane, toluene, etc.; the catalyst is an organic small molecule catalyst, such as pyridine.
[0014] In the above technical solution, the chemical structure of the DA'D type conjugated core is one of the following structural formulas:
[0015]
[0016] The electron withdrawing end groups are independently selected from one of the following compounds:
[0017]
[0018] In the above structural formula, the selection of substituents (X1, X2, X3, X4, B1-B8, R1, R2, R3, R4, R5) is the same as the selection of substituents in Formulae 1 to 6 above.
[0019] The present invention discloses the application of the non-fullerene acceptor with spatially confined crystallization in the preparation of an organic solar cell or an active layer of an organic solar cell.
[0020] The present invention discloses the application of the above-mentioned non-fullerene acceptor with spatially confined crystallization performance in improving the efficiency of ultra-thick active layer solar cells. Generally, the thickness of the ultra-thick active layer is greater than 100nm, further greater than 150nm, further greater than 200nm, and further greater than 250nm.
[0021] In the present invention, the non-fullerene acceptor with spatially confined crystallization having an ethylene glycol group means that in the structural formula of the non-fullerene acceptor with spatially confined crystallization, there is a substituent which is an ethylene glycol group, and the substituent is represented by R1, R2, R3, R4, and R5. The ethylene glycol group can be a monoethylene glycol group, such as -(CH2CH2O)CH3, or an oligoethylene glycol group, such as -(CH2CH2O) m CH3, m is 2 to 10. In the chemical structure of the non-fullerene acceptor with spatially confined crystallization, the ethylene glycol group may be one or more. n H 2n+1 represents a branched alkane or a straight alkane, and n is preferably 3-18, more preferably 5-15.
[0022] The non-fullerene acceptor with spatially confined crystallization performance of the present invention comprises an asymmetric oligoethylene glycol (OEG) chain, whose high crystallinity can induce additional crystal nucleation and promote molecular assembly, and help increase crystal nucleation sites, which can stimulate molecular assembly through molecular interactions between acceptors. Therefore, the acceptor of the present invention plays a role in enhancing crystallinity and optimizing vertical phase separation in the active layer. As an example, based on the spatially confined crystallization acceptor of the present invention as the guest, D18-Cl:N3 as the main component, the PCE based on D18-Cl:N3:AT-β2O (100nm) reached 20.24%, the open circuit voltage was 0.892V, and the filling factor was 80.34%; when the film thickness was 130nm, the PCE of OSCs reached a record 20.82% (certified as 20.43%). In addition, when the film thickness is further increased to 250nm and 400nm, the device can still maintain an efficiency of up to 19.15% and 17.93%, which indicates that the addition of the spatially confined crystalline receptor significantly improves the independence of film thickness. The present invention also uses the spatially confined crystalline receptor to prepare large-area components, and the PCE of the device based on D18-Cl:N3:AT-β2O (250nm) is as high as 18.36% (certified as 18.04%).
[0023] The present invention discloses the application of the above-mentioned non-fullerene acceptor with spatially confined crystallization performance in the preparation of organic solar cells. Specifically, the non-fullerene acceptor with spatially confined crystallization performance of the present invention is used as a guest to prepare an organic solar cell active layer, especially to prepare a thick-film organic solar cell active layer, so as to obtain high-performance small-area devices and large-area components; when the non-fullerene acceptor with spatially confined crystallization performance disclosed by the present invention is blended with a main active layer, a more stable microstructure and morphology can be obtained, and the obtained device has better working stability.
[0024] The present invention discloses an active layer material for an organic solar cell, comprising the above-mentioned non-fullerene acceptor with spatially confined crystallization; further comprising a Y series acceptor and a donor material. The above-mentioned non-fullerene acceptor with spatially confined crystallization is a guest material, and the Y series acceptor and the donor material are host materials to form an active layer for a solar cell; the donor material is a conjugated polymer or a conjugated organic small molecule, and the Y series acceptor is 2,2'-(((12,13-bis(3-ethylheptyl)-3,9-diundecyl-12,13-dihydro-[1,2,5]thiadiazo[3,4-e]thieno[2”,3”:4’,5’]thieno[2’,3’:4,5]pyrrolo[3,2-g]thieno[2’,3’:4,5]thieno[3,2-b]indole-2,10-bis(5,6-difluoro-3-(dicyano)- 2,2'-(((12,13-bis(2-ethylhexyl)-3,9-diundecyl-12,13-dihydro-[1,2,5]thiadiazo[3,4-e]thieno[2",3":4',5']thieno[2',3':4,5]pyrrolo[3,2-g]thieno[2',3':4,5]thieno[3,2-b]indole-2,10-bis(5,6-difluoro-3-(dicyanomethyl)indene-1-one)(Y6), 2,2'-(((12,13-bis(2-butyloctyl)-3,9-dinonyl-12,13-dihydro-[1,2,5]thiadiazo[3,4-e]thieno[2",3":4',5']thieno[2',3':4,5]pyrrolo[3,2-g]thieno[2',3':4,5]thieno[3,2-b]indole-2,10-bis(5,6-difluoro-3-(dicyanomethyl)indene-1-one)(Y7), oxadiazolo[3,4-e]thieno[2”,3”:4’,5’]thieno[2’,3’:4,5]pyrrolo[3,2-g]thieno[2’,3’:4,5]thieno[3,2-b]indole-2,10-bis(5,6-dichloro-3-(dicyanomethylidene)indene-1-one)(BTP-eC9), 2,2’-(((12,13-bis(2-ethylhexyl)-3,9-bis(2-butyloctyl)-12,13-dihydro-[1,2,5]thiadiazolo[3,4-e]thieno[2”,3”:4’,5’]thieno[2’,3’:4,5]pyrrolo[3,2-g]thieno[2 ',3':4,5]thieno[3,2-b]indole-2,10-bis(5,6-difluoro-3-(dicyanomethylidene)indene-1-one)(L8-BO), 2,2'-(((12,13-bis(2-decyldodecyl)-3,9-diundecyl-12,13-dihydro-[1,2,5]thiadiazo[3,4-e]thieno[2",3":4',5']thieno[2',3':4,5]pyrrolo[3,2-g]thieno[2',3':4,5]thieno[3,2-b]indole-2,10-bis(5,6-difluoro-3-(dicyanomethylidene)indene-1-one)(DTY6), etc.;The donor material is poly[[4,8-bis(5-(2-ethylhexyl)-4-chlorothiophene-2-yl)benzo[1,2-b:4,5-b']dithiophene-2,6-diyl][5,8-bis(4-(2-butyloctyl)thiophene-2-yl)dithieno[3',2':3,4;2",3":5,6]benzo[1,2-c][1,2,5]thiadiazolediyl]](D18-Cl), poly[(2,6-(4,8-bis(5-(2-ethylhexyl-3-fluoro)thiophene-2-yl)-benzo][1,2-b:4,5-b']dithiophene))-alt -(5,5-(1',30-bis-2-thiophene-50,7'-bis(2-ethylhexyl)benzo[1',2'-c:4',50-c']dithiophene-4,8-dione) (PM6), poly[[4,8-bis(5-(2-ethylhexyl)-4-fluorothiophene-2-yl)benzo[1,2-b:4,5-b']dithiophene-2,6-diyl][5,8-bis(4-(2-butyloctyl)thiophene-2-yl)dithieno[3',2':3,4;2",3":5,6]benzo[1,2-c][1,2,5]thiadiazolediyl]] (D18), etc.;
[0025] The invention discloses an organic solar cell, comprising an active layer, a hole transport layer, an electron transport layer and an electrode; the active layer comprises the above-mentioned non-fullerene acceptor with spatially confined crystallization performance.
[0026] The present invention discloses a method for preparing the above-mentioned organic solar cell, comprising the following steps: sequentially preparing a hole transport layer, an active layer, an electron transport layer and an electrode on a conductive substrate to obtain an organic solar cell; the active layer comprises the above-mentioned non-fullerene acceptor with spatially confined crystallization performance.
[0027] In the present invention, when preparing the active layer, a conjugated polymer is used as the donor material, a Y series conjugated small molecule (such as N3, L8-BO, BTP-eC9, star molecule Y6), and the above-mentioned non-fullerene with spatially confined crystallization performance are used as the acceptor component, and different processing solvents are used to prepare a mixed solution containing the donor material and the acceptor material, and the non-fullerene acceptor with spatially confined crystallization performance, and then the active layer film is prepared by conventional solution processing, and the conventional solution processing method is spin coating or scraping. In the above-mentioned mixed solution, the processing solvent is chloroform (CF), diphenyl ether (DPE), toluene (TL), p-xylene (PX) or o-xylene (OX); the concentration of the donor material is 5 to 20 mg / mL; the mass fraction of the above-mentioned non-fullerene with spatially confined crystallization performance in the donor material is 0 to 50%, preferably 10 to 40%, and more preferably 15 to 30%. The creativity of the present invention lies in using the above-mentioned non-fullerene acceptor with spatially confined crystallization properties as the third component and the existing light-emitting layer material (composed of existing donor materials and acceptor materials) as the main body to achieve an active layer with film thickness independence, and the non-fullerene acceptor with spatially confined crystallization properties has good compatibility with different active layer systems, processing solvents, processing methods and post-processing processes.
[0028] In the organic solar cell of the present invention, the electron transport layer, the hole transport layer and the electrode are existing products, and the specific preparation method of each layer is also conventional technology. For example, the hole transport layer material is PEDOT:PSS, and the electron transport layer material is C 60 / BCP, the electrode is silver, and the thickness of the active layer is 100-400nm, especially 200-400nm. The creativity of the present invention lies in the disclosure of a new material as a non-fullerene acceptor with spatially confined crystallization performance, which can obtain a high-performance battery with record efficiency and still maintain high PCE and other properties in the case of thick film.
[0029] Beneficial effects of the present invention:
[0030] 1. The present invention creatively introduces an asymmetric oligoethylene glycol chain into a non-fullerene receptor to obtain a non-fullerene receptor with spatially confined crystallization performance. Compared with the existing high-efficiency non-fullerene receptor, it can regulate the molecular assembly process of other receptors, induce other receptors to preferentially form a face-on orientation, and enhance long-range ordered molecular stacking (higher crystallinity);
[0031] 2. After the non-fullerene receptor with spatially confined crystallization performance disclosed in the present invention is incorporated into the host as a guest component, the receptor nucleation and molecular assembly can be regulated, the crystallinity of the active layer is improved, and the vertical phase separation is optimized, and high-performance OSCs are prepared in the case of thick films, which solves the problem of thin film pinholes caused by low film thickness in the preparation of large-area devices, lays a foundation for the preparation of large-area devices, and has considerable application potential in the printing of large-area devices;
[0032] 3. When the non-fullerene acceptor with spatially confined crystallization performance disclosed in the present invention is blended with a main donor-acceptor material, a more stable microstructure and morphology can be obtained, and the obtained device has better working stability;
[0033] 4. The non-fullerene acceptor with spatially confined crystallization properties disclosed in the present invention can be added as a guest molecule to different active layer systems (with different solvents, post-treatment processes and processing methods), and both the improvement of photoelectric performance and film thickness independence can be achieved. These results show that the non-fullerene acceptor with spatially confined crystallization properties is universal and can be compatible with different active layers, solvents, processing methods and post-treatments. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 is the hydrogen nuclear magnetic resonance spectrum of AT-β2O in Example X;
[0035] Figure 2 is the carbon NMR spectrum of AT-β2O in Example X;
[0036] Figure 3 is the matrix-assisted laser desorption ionization time-of-flight mass spectrometry of AT-β2O in Example X;
[0037] Figure 4 is the thermal gravimetric curve of AT-β2O in Example X;
[0038] Figure 5 is the cyclic voltammetry curve of AT-β2O in Example X;
[0039] Figure 6 Scattering curves of N3, AT-β2O and N3:AT-β2O along a, IP and b, OOP directions in Example 1, c, the pole figure extracted by (010) diffraction of the corresponding film;
[0040] Figure 7 For the AM 1.5G 100mW cm in Example 2 -2 JV curves of devices with different thicknesses of D18-Cl:N3 and D18-Cl:N3:AT-β2O processed by chloroform / diphenyl ether under irradiation;
[0041] Figure 8 The cross-sectional SEM images and corresponding EDS spectra of D18-Cl:N3 (400 nm) and D18-Cl:N3:AT-β2O (400 nm) processed by chloroform / diphenyl ether deposited on ITO in Example 2;
[0042] Fig. 9 The molecular structures of PM6, Y6, BTP-eC9, D18, L8-BO and DTY6 in Example 3;
[0043] Fig.10 For the AM 1.5G 100mW cm in Example 3 -2 JV curves of devices based on PM6:Y6 and PM6:Y6:AT-β2O with different thicknesses processed by chloroform under irradiation;
[0044] Fig.11 For example, in the fourth embodiment, the AM 1.5G 100mW cm -2 JV curves of devices with different thicknesses of PM6:BTP-eC9 and PM6:BTP-eC9:AT-β2O processed by chloroform under irradiation;
[0045] Fig.12 For the AM 1.5G 100mW cm in Example 5 -2 JV curves of devices based on PM6:L8-BO and PM6:L8-BO:AT-β2O with different thicknesses processed by chloroform under irradiation;
[0046] Fig.13 For example, in the sixth embodiment, the AM 1.5G 100mW cm -2 JV curves of devices with different thicknesses of PM6:L8-BO and PM6:L8-BO:AT-β2O processed in toluene under irradiation;
[0047] Fig.14 For example, in Example 7, the AM 1.5G 100mW cm -2 JV curves of devices with different thicknesses of D18:L8-BO and D18:L8-BO:AT-β2O processed in p-xylene under irradiation;
[0048] Fig.15 In Example 8, the AM 1.5G 100mW cm -2 JV curves of devices with different thicknesses of PM6:DTY6 and PM6:DTY6:AT-β2O processed in o-xylene under irradiation;
[0049] Fig.16For the AM 1.5G 100mW cm in Example 9 -2 JV curves of OSC components based on D18-Cl:N3 and D18-Cl:N3:AT-β2O thin films (250 nm) processed in chloroform / diphenyl ether under irradiation;
[0050] Fig.17 This is the LBIC imaging image of the large area component in Example 9;
[0051] Fig.18 is the molecular formula of the comparative material BT-β2O in the comparative example;
[0052] Fig.19 For example, in AM 1.5G 100mW cm -2 J-V curves of devices with different thicknesses of D18-Cl:N3:AT-β2O and D18-Cl:N3:BT-β2O processed in chloroform / diphenyl ether under irradiation. DETAILED DESCRIPTION
[0053] Currently, most OSCs adopt a bulk heterojunction (BHJ) structure, in which electron donors (D) and electron acceptors (A) are mixed to form a bicontinuous interpenetrating D / A network. The light-generated excitons initially diffuse through the D / A phase to reach the DA interface, and then, driven by the energy difference between the donor and acceptor materials, dissociate into charge carriers by overcoming the exciton binding energy. Therefore, the exciton diffusion length (L D ) has an important influence on device performance because it determines the density of excitons that can reach the DA interface. However, L in organic semiconductors D The domain size (usually ~10-30 nm) is much shorter than that of pure domains, and this difference leads to severe charge recombination. In addition, in thicker active layers, the crystallization of the upper small molecule acceptor (SMA) is only weakly dependent on the substrate-induced forces, thus forming a less crystalline SMA phase. The resulting high-energy disorder hinders exciton transitions and suppresses Exciton diffusion further reduces L D On the other hand, more dissociated carriers are generated at the bottom of the active layer (because the incident light hits the transparent electrode side), which results in the electrons in the forward thick film device having to travel a much longer distance to the top electrode (cathode) than the holes to the anode.
[0054] To solve this problem, the present invention introduces a vertical spatial confinement crystallization (VSC) strategy based on functional receptors; this VSC strategy can coordinate the regulation of the crystallization and vertical phase separation of SMA. The designed receptor AT-β2O with spatial confinement crystallization performance has an asymmetric molecular configuration with a hydrophilic oligoethylene glycol (OEG) chain at the β position of the thiophene unit. This design allows AT-β2O to interact with the secondary bonds of the receptor material and regulate the solubility of the active layer material, thereby regulating the crystallization order of the components in the BHJ active layer, thereby achieving spatial confinement crystallization of the receptor material. This precise regulation of crystallization dynamics allows the active layer to have better crystallinity and good vertical phase separation (with a receptor-rich phase near the cathode interface), thereby reducing energy disorder and enhancing exciton diffusion. Using this effective regulation strategy, single-junction OSCs achieved a record PCE of 20.82% (certified efficiency 20.43%). In particular, the OSCs active layer is independent of film thickness, and its PCE remains at 19.15% (certified 18.81%) and 17.93% when the film thickness increases to 250nm and 400nm, respectively. A pinhole-free large area (15.03cm 2 ) component, with a record PCE of 18.36% (certified as 18.04%). It is worth noting that the VSC strategy significantly improves the device's operating stability: at 100mW cm -2 Under white light-emitting diode (LED) illumination, the OSCs maintained 83% of their initial PCE after aging at the maximum power point (MPP) for 1200 h. Similar experimental results were observed in parallel experiments with different active layers, solvents, processing methods, and post-treatments, demonstrating the universality of the proposed spatially confined crystallized receptor.
[0055] The structural formula of the non-fullerene acceptor material (AT-β2O) with vertical confined space crystallization is:
[0056]
[0057] The preparation process of the above AT-β2O is shown above, and the specific preparation method is as follows:
[0058] Sodium metal (3.36 g, 0.15 mol) was added to diethylene glycol monomethyl ether (52.64 g, 0.44 mol) and heated at 100°C for more than 6 h. After cooling naturally to room temperature, copper oxide (7.0 g, 88 mmol) and potassium iodide (0.66 g, 4 mmol) were added. Under nitrogen protection, 3-bromothiophene [3,2-B] thiophene (8.06 g, 36 mmol) was added dropwise to the reaction system. The mixture was stirred at 110°C overnight. Petroleum ether / ethyl acetate (volume ratio 5:1) was used as the eluent. 3-[2-(2-methoxyethoxy)]ethoxythieno[3,2-b] thiophene was separated by silica gel column chromatography to obtain a light yellow liquid 3-[2-(2-methoxyethoxy)]ethoxythieno[3,2-b] thiophene.
[0059] Under nitrogen protection, a tetrahydrofuran solution (50 mL) of 3-[2-(2-methoxyethoxy)]ethoxythieno[3,2-b]thiophene (5 g, 19 mmol) was cooled to -98°C with liquid nitrogen, and then n-butyl lithium solution (9.3 mL, 23.5 mmol) was added dropwise. After reacting for 2 h, tributyltin chloride (8.2 g, 24.7 mmol) was added and reacted at room temperature overnight. Water was added to quench the reaction to obtain a brown-yellow liquid 3-[2-(2-methoxyethoxy)]ethoxythieno[3,2-b]thiophene tributyltin;
[0060] Under nitrogen protection, 4,7-dibromo-5,6-dinitrobenzo[c][1,2,5]thiadiazole (4.65 g, 12 mmol), 3-[2-(2-methoxyethoxy)]ethoxythieno[3,2-b]thiophene tributyltin (10.6 g, 19 mmol), 3-undecylthieno[3,2-b]thiophene (7.07 g, 12 mmol) and Pd(PPh3)Cl2 (0.62 g, 0.88 mmol) were dissolved in anhydrous toluene (50 mL) and stirred at 110°C overnight. The reaction mixture was cooled to room temperature and then concentrated under reduced pressure. Silica gel column chromatography was used for separation, and petroleum ether / ethyl acetate (volume ratio 3:1) was used as the eluent to obtain a red solid 4-[6-(2-methoxyethoxy)ethoxythieno[3,2-b]thiophen-2-yl]-5,6-dinitro-7-(6-undecyl)thieno[3,2-b]thiophen-2-ylbenzo[c][1,2,5]thiadiazole;
[0061] Under nitrogen protection, 4-[6-(2-methoxyethoxy)ethoxythieno[3,2-b]thien-2-yl]-5,6-dinitro-7-(6-undecyl)thieno[3,2-b]thien-2-ylbenzo[c][1,2,5]thiadiazole (2.83 g, 4 mmol) and triphenylphosphine (9.38 g, 36 mmol) were dissolved in o-dichlorobenzene (10 mL) and heated at 180 °C. The mixture was heated at room temperature for 4 h, cooled naturally to room temperature, and then added dropwise into anhydrous methanol (200 mL) to obtain a red solid 3-[2-(2-methoxyethoxy)ethoxy]-9-undecyl-12,13-dihydro-[1,2,5]thiadiazo[3,4-e]thieno[2',3':4',5']thieno-2,2-g]thieno[2,3':4,5]thieno[3,2-b]indole;
[0062] Under nitrogen protection, 3-[2-(2-methoxyethoxy)ethoxy]-9-undecyl-12,13-dihydro-[1,2,5]thiadiazo[3,4-e]thieno[2',3':4',5']thieno-2,2-g]thieno[2,3':4,5]thieno[3,2-b]indole (2.83 g, 4 mmol), isooctane bromide (12.68 g, 65 mmol), cesium carbonate (11.9 g, 37 mmol), and potassium iodide (12.12 g, 73 mmol) were dissolved in DMF (120 mL) and heated at 110°C overnight. The reaction mixture was naturally cooled to room temperature and then concentrated under reduced pressure. Silica gel column chromatography was used for separation, and petroleum ether / ethyl acetate (volume ratio 5:1) was used as the eluent to obtain a red oily liquid 12,13-bis(2-ethylhexyl)-3-[2-(2-methoxyethoxy)ethoxy]-9-undecyl-12,13-dihydro-[1,2,5]thiadiazo[3,4-e]thieno[2',3':4',5']thieno[3',3':4,5]pyrrolo[3,2-g]thieno[4,3':4,5]thieno[3,2-b]indole;
[0063] Under nitrogen protection, phosphorus oxychloride (2.99 g, 20 mmol) was added dropwise to DMF (2.14 g, 30 mmol) and stirred at 0°C for 2 h. 12,13-Bis(2-ethylhexyl)-3-[2-(2-methoxyethoxy)ethoxy]-9-undecyl-12,13-dihydro-[1,2,5]thiadiazole[3,4-e]thieno[2',3':4',5']thieno[3',3':4,5]pyrrolo[3,2-g]thieno[4,3':4,5]thieno[3,2-b]indole (1 g, 1 mmol) was dissolved in chloroform (20 mL) and added to the reaction system. The mixture was heated at 75°C overnight. The reaction mixture was cooled to room temperature and then concentrated under reduced pressure. Silica gel column chromatography was used for separation, and petroleum ether / ethyl acetate (volume ratio of 5:1) was used as the eluent to obtain a red oily liquid 12,13-bis(2-ethylhexyl)-3-[2-(2-methoxyethoxy)ethoxy]-9-undecyl-12,13-dihydro-[1,2,5]thiadiazole[3,4-e]thieno[2',3':4',5']thieno[3',3':4,5]pyrrolo[3,2-g]thieno[20',3':4,5]thieno[3,2-b]indole-2,10-dicarbaldehyde;
[0064] Under nitrogen protection, 12,13-bis(2-ethylhexyl)-3-[2-(2-methoxyethoxy)ethoxy]-9-undecyl-12,13-dihydro-[1,2,5]thiadiazo[3,4-e]thieno[2',3':4',5']thieno[3',3':4,5]pyrrolo[3,2-g]thieno[20',3':4,5]thieno[3,2-b]indole-2,10-dicarbaldehyde (0.6 g, 0.6 mmol) and 2-(5,6-difluoro-3-oxo-2,3-dihydro-1H-inden-1-ylidene)malononitrile (0.42 g, 1.8 mmol) were dissolved in chloroform (10 mL), pyridine (1 mL) was added, and the mixture was stirred at 65°C overnight. After cooling naturally to room temperature, the mixture was poured into methanol and filtered. The residue was purified by silica gel column chromatography using dichloromethane as the eluent to obtain a blue-black solid 2,2'-(2Z,2'Z)-[(12,13-bis(2-ethylhexyl)]-3-[2-(2-methoxyethoxy)ethoxy]-9-undecyl 12,13-dihydro-[1,2,5]thiadiazole [3,4-e]thieno [2", 3": 4',5']thieno [3', 3': 4,5]pyrrolo [3', 3': 4,5]thieno [4,5]thieno [3,2-b]indole) bis(methylenediene)) (5-difluoro-3-oxo-2-dihydro-1H-indene) yield (75%): 1HNMR(600MHz, CDCl3)δ9.32(s,1H),9.12(s,1H),8.54–8.47(m,2H),7.73–7.65(m, 2H),4.97(s,2H),4.78(m,4H),4.07(t,2H),3.82(t,2H),3.65(t,2H),3.42(s,3H) ,3.21(t,2H),2.11(m,2H),1.87(m,2H),1.50(m,2H),1.37(m,2H),1.26–1.25(m,1 2H),1.20–1.19(m,4H),1.06–1.04(m,12H),0.87–0.85(t,3H),0.78–0.66(m,12H). 13 C NMR (150MHz, CDCl3) δ186.58,186.12,162.04,158.51,153.83,147.46,147.34,145.20,137.82,137. 53,137.16,135.84,135.20,134.37,133.56,133.26,131.83,130.41,128.33,120.06,117.67,114.65 ,113.80,113.03,112.24,73.04,71.95,70.79,69.39,68.81,67.37,59.08,55.67,40.47,31.91,31.21,29.82,29.65,29.62,29.51,29.45,29.34,27.79,27.62,23.23,22.83,22.69,14.12,13.77,10.20.
[0065] The raw materials of the present invention are all existing products, and the specific preparation operations and testing methods are all conventional methods in the art. Unless otherwise specified, the thickness of the hole transport layer is 35 nm.
[0066] Embodiment 1
[0067] An active layer material for an organic solar cell, comprising the above-mentioned non-fullerene acceptor, other Y series acceptors and donor materials. Taking N3 and AT-β2O acceptors and D18-Cl donor as examples:
[0068] (1) An indium tin oxide (ITO) conductive glass sheet was ultrasonically cleaned with ethanol, acetone, and isopropanol, and then dried and spin-coated with a layer of PEDOT:PSS at 6000 rpm as a hole transport layer (35 nm). The layer was then heated and dried at 150°C for 15 min and placed in a N2 glove box for later use.
[0069] (2) N3, D18-Cl, AT-β2O or N3 and D18-Cl were added to chloroform / diphenyl ether to prepare an active layer solution. The specific preparation process was as follows: the ratio of D18-Cl:N3:AT-β2O was 1:1.4:0, 1:1.3:0.1, 1:1.2:0.2 and 1:1.1:0.3 (w / w, CF / DPE (volume ratio 96:4%), and the concentration of the donor was 5 mg mL -1 Subsequently, the active layer solution was spin-coated on the PEDOT:PSS layer (without any post-treatment) to prepare the active layer.
[0070] The self-assembly process of AT-β2O molecules was analyzed by grazing incidence wide-angle X-ray scattering (GIWAXS). Figure 6 ). When a small amount of AT-β2O is mixed with N3, the diffraction signal of N3 becomes stronger in both IP(100) and OOP(010) directions, indicating that the order of N3 along the side chain and π-π stacking directions is significantly increased. This shows that AT-β2O molecules can also regulate the assembly of N3 molecules in the mixture. As shown in Table 1-3, the ratio of face-on orientation to edge-on orientation (A z / A xy ) and the increase in crystal coherence lengths (CCLs) (along the IP (100) and OOP (010) directions) confirm that AT-β2O induces N3 to preferentially form a face-on orientation with higher crystallinity.
[0071] Table 1 Figure 6 Face-on (A z ) and edge-on(A xy ) Orientation ratio
[0072] film <![CDATA[A z (%)]]> <![CDATA[A xy (%)]]> <![CDATA[A z / A xy ]]> N3 71.46 28.54 2.50 AT-β2O 75.49 24.51 3.08 N3:AT-β2O 80.81 19.19 4.21
[0073] Table 2 Figure 6 The (100) diffraction peak positions and corresponding CCL values of different films
[0074]
[0075] Table 3 Figure 6 The out-of-plane (010) diffraction peak positions and corresponding CCL values of different films
[0076]
[0077] (3) Finally, in 1×10 -6 Under the condition of vacuum evaporation at 1000 mbar, C was deposited on the active layer in sequence. 60 (10nm) / BCP(5nm) / Ag(100nm) electrode.
[0078] The active area of the device is 6.28mm 2 . In AM 1.5G 100mW cm -2 The performance of the above-mentioned different organic solar cells was tested under irradiation conditions, and the corresponding performance parameters were obtained, as shown in Table 4.
[0079] Table 4 Photovoltaic performance parameters of OSCs based on different ratios of D18-Cl:N3:AT-β2O
[0080]
[0081] This embodiment adopts ITO / PEDOT:PSS / active layer / C 60 OSCs were prepared with the forward structure of / BCP / Ag. The device based on D18-Cl:N3:AT-β2O (1:1.2:0.2w / w / w) showed the highest PCE. The PCE of OSC based on D18-Cl:N3 (100nm) was 18.11%, which is consistent with that reported in the previous article. In contrast, the PCE of OSC based on D18-Cl:N3:AT-β2O (1:1.2:0.2) active layer was 20.24% (certified efficiency was 19.99%), the FF was improved to 80.34%, and the open circuit voltage (V oc ) is 0.892V.
[0082] After further varying the active layer thickness, the PCE of OSCs based on D18-Cl:N3:AT-β2O (1:1.2:0.2, 130 nm) reached a record high of 20.82% (certified efficiency 20.43%), which is the highest reported value for OSCs based on thin (~100 nm) active layers.
[0083] Embodiment 2
[0084] An active layer material for an organic solar cell, comprising the above-mentioned non-fullerene acceptor, other Y series acceptors and donor materials. Taking N3 and AT-β2O acceptors and D18-Cl donor materials as examples:
[0085] (1) preparing an indium tin oxide (ITO) hole transport layer as in Example 1, and keeping the N2 glove box ready for use;
[0086] (2) N3, D18-Cl, AT-β2O or N3 and D18-Cl were added to chloroform / diphenyl ether to prepare an active layer solution. The specific preparation process was as follows: the ratio of D18-Cl:N3:AT-β2O was 1:1.2:0.2 (w / w, CF / DPE (volume ratio 96:4%), and the concentration of the donor was 5, 10, and 15 mg mL when preparing active layers of different thicknesses. -1), and then spin-coating the active layer solution on the PEDOT:PSS layer to obtain active layers with thicknesses of 100 (Example 1), 250, and 400 nm (without post-treatment);
[0087] (3) Finally, in 1×10 -6 Under the condition of vacuum evaporation at 1000 mbar, C was deposited on the active layer in sequence. 60 (10nm) / BCP(5nm) / Ag(100nm) electrode.
[0088] The active area of the device is 6.28mm 2 . In AM 1.5G 100mW cm -2 The performance of the above different organic solar cells was tested under illumination conditions to obtain current-voltage curves, such as Figure 7 As shown in Table 5, the corresponding battery performance parameters are obtained.
[0089] Table 5 Photovoltaic performance parameters of OSCs based on D18-Cl:N3 and D18-Cl:N3:AT-β2O with different film thicknesses
[0090]
[0091] c Certified efficiency for SIMIT in Shanghai, China.
[0092] Cross-sectional scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDS) were used to investigate the vertical phase separation in 400 nm thick films. Figure 8 It can be seen that the F-rich layer appears at the top of D18-Cl:N3:AT-β2O (400nm), representing N3 and AT-β2O, and the Cl-rich layer is distributed in the middle and bottom, representing D18-Cl. The results show that the vertical components are distributed in a gradient, with the top being the acceptor-rich phase and the middle and bottom being the donor-rich phase. The D18-Cl:N3 (400nm) film shows a more uniform phase distribution in the vertical direction. This shows that AT-β2O helps to optimize the vertical phase separation inside the thick film active layer.
[0093] Figure 7 Table 5 shows the JV curves and photovoltaic parameters of D18-Cl:N3 and D18-Cl:N3:AT-β2O at different thicknesses. When the thickness of the active layer based on D18-Cl:N3 increases to 250nm and 400nm, the filling factor and PCE decrease significantly. In contrast, after adding the spatially confined crystallization characteristic acceptor, the active layer based on D18-Cl:N3:AT-β2O has film thickness independence; the device efficiency with an active layer thickness of 250nm is 19.15% (certified efficiency is 18.81%), and the short-circuit current density (J sc) increases to 28.56 mA cm -2 ,V oc The PCE of the device was maintained at 17.93% when the thickness of the active layer was further increased to 400 nm, which was significantly higher than the 12.45% of the device without AT-β2O. The results show that the spatially confined crystallized non-fullerene acceptor can improve the thickness independence of the active layer. These results indicate that the proposed VSC strategy is conducive to the large-scale production of OSCs using high-throughput roll-to-roll technology.
[0094] Embodiment 3
[0095] An organic solar cell, the active layer material of which includes the above-mentioned non-fullerene acceptor, other Y series acceptors (Y6) and donor material (PM6). The preparation method of the organic solar cell is as follows:
[0096] (1) preparing an indium tin oxide (ITO) hole transport layer as in Example 1, and keeping the N2 glove box ready for use;
[0097] (2) Then, an active layer film was prepared on the hole transport layer by a spin method. The specific preparation process of the active layer solution was as follows: the ratio of PM6:Y6:AT-β2O(CF) was 1:1.2:0 and 1:1:0.2 (w / w), the additive was 0.5% CN, and the concentration of the donor when preparing active layers of different thicknesses was 7.27, 11.5, and 15 mg mL -1 , then, the active layer solution was spin-coated on the PEDOT:PSS layer to obtain active layers with thicknesses of 100, 250, and 400 nm (the active layer did not require any post-treatment);
[0098] (3) Finally, in 1×10 -6 Under the condition of vacuum evaporation at 1000 mbar, C was deposited on the active layer in sequence. 60 (10nm) / BCP(5nm) / Ag(100nm) electrode. The active area of the device is 6.28mm 2 .
[0099] Fig. 9 The molecular structures of PM6, Y6, BTP-eC9, D18, L8-BO and DTY6 are shown in Figure 2. The performance of the organic solar cells was tested at AM 1.5G 100mW cm -2 The current-voltage curve is measured under illumination conditions, such as Fig.10 As shown, the corresponding battery performance parameters are obtained, see Table 6. When the thickness is further increased to 400nm, the ternary device also shows a PCE that is better than the binary device. It can be seen that the spatially confined crystallized non-fullerene acceptor plays a particularly prominent role in the preparation of thick film devices.
[0100] Table 6 Photovoltaic performance parameters of OSCs based on PM6:Y6 and PM6:Y6:AT-β2O with different film thicknesses
[0101]
[0102]
[0103] Embodiment 4
[0104] An organic solar cell, whose active layer material is the above-mentioned non-fullerene acceptor, other Y series acceptors (BTP-eC9) and donor material (PM6), and the preparation method is as follows:
[0105] (1) preparing an indium tin oxide (ITO) hole transport layer as in Example 1, and keeping the N2 glove box ready for use;
[0106] (2) Then, an active layer film was prepared on the hole transport layer by spin coating. The specific preparation process of the active layer solution was as follows: the ratio of PM6:BTP-eC9:AT-β2O (chloroform / diphenyl ether processing) was 1:1.15:0 and 1:1.05:0.1 (w / w), and the additive was 0.5% DIO. When preparing active layers of different thicknesses, the concentrations of the donor were 7, 11, and 15.3 mg mL -1 , Subsequently, the active layer solution was spin-coated on the PEDOT:PSS layer to obtain active layers with thicknesses of 100, 250, and 400 nm (without post-treatment);
[0107] (3) Finally, in 1×10 -6 Under the condition of vacuum evaporation at 1000 mbar, C was deposited on the active layer in sequence. 60 (10nm) / BCP(5nm) / Ag(100nm) electrode. The active area of the device is 6.28mm 2 .
[0108] The performance of the organic solar cell was tested at AM 1.5G 100mW cm -2 The current-voltage curve is measured under illumination conditions, such as Fig.11 As shown in Table 7, the corresponding battery performance parameters are obtained.
[0109] Table 7 Photovoltaic performance of OSCs of PM6:BTP-eC9 and PM6:BTP-eC9:AT-β2O with different film thicknesses
[0110]
[0111] Embodiment 5
[0112] An organic solar cell, the active layer material of which includes the above-mentioned non-fullerene acceptor, other Y series acceptors (L8-BO) and donor materials (PM6), is prepared as follows:
[0113] (1) preparing an indium tin oxide (ITO) hole transport layer as in Example 1, and keeping the N2 glove box ready for use;
[0114] (2) Then, an active layer film was prepared on the hole transport layer by spin coating. The specific preparation process of the active layer solution was as follows: the ratio of PM6:L8-BO:AT-β2O(CF) was 1:1.2:0 and 1:1.1:0.1 (w / w), the additive was 0.25% DIO, and the concentration of the donor when preparing active layers of different thicknesses was 7, 11, and 15 mg mL -1 , then, the active layer solution was spin-coated on the PEDOT:PSS layer to obtain active layers with thicknesses of 100, 250, and 400 nm (without any post-treatment);
[0115] (3) Finally, in 1×10 -6 Under the condition of vacuum evaporation at 1000 mbar, C was deposited on the active layer in sequence. 60 (10nm) / BCP(5nm) / Ag(100nm) electrode. The active area of the device is 6.28mm 2 .
[0116] The performance of the above different organic solar cells was tested at AM 1.5G 100mW cm -2 Measured under irradiation conditions, such as Fig.12 As shown, the corresponding battery performance parameters are obtained, see Table 8. The results show that spatially confined crystallized non-fullerene acceptors provide great potential for the preparation of efficient ternary thick-film OSCs.
[0117] Table 8 Photovoltaic performance parameters of OSCs of PM6:L8-BO and PM6:L8-BO:AT-β2O with different film thicknesses
[0118]
[0119] Embodiment 6
[0120] An organic solar cell, the active layer material of which includes the above-mentioned non-fullerene acceptor, other Y series acceptors (L8-BO) and donor materials (PM6), is prepared as follows:
[0121] (1) preparing an indium tin oxide (ITO) hole transport layer as in Example 1, and keeping the N2 glove box ready for use;
[0122] (2) Then, an active layer film was prepared on the hole transport layer by spin coating. The specific preparation process of different active layer solutions was as follows: the ratio of PM6:L8-BO:AT-β2O (TL) was 1:1.2:0 and 1:1.1:0.1 (w / w), the additive was 0.25% DIO, and the concentration of the donor when preparing active layers of different thicknesses was 8-16 mg mL -1 , then the active layer solution was spin-coated on the PEDOT:PSS layer to obtain active layers with thicknesses of 100, 250, and 400 nm (the active layer did not require any post-treatment);
[0123] (3) Finally, in 1×10 -6 Under the condition of vacuum evaporation at 1000 mbar, C was deposited on the active layer in sequence. 60 (10nm) / BCP(5nm) / Ag(100nm) electrode. The active area of the device is 6.28mm 2 .
[0124] The performance of the above different organic solar cells was tested at AM 1.5G 100mW cm -2 The current-voltage curve is measured under illumination conditions, such as Fig.13 As shown, the corresponding cell performance parameters are obtained, see Table 9. The higher FF indicates that the addition of spatially confined crystallized non-fullerene acceptors is essential to maintain high photovoltaic performance in thick film devices.
[0125] Table 9 Performance of OSCs of PM6:L8-BO(TL) and PM6:L8-BO:AT-β2O(TL) with different film thicknesses
[0126]
[0127] Embodiment 7
[0128] An organic solar cell, the active layer material of which includes the above-mentioned non-fullerene acceptor, other Y series acceptors (L8-BO) and donor materials (D18), is prepared as follows:
[0129] (1) preparing an indium tin oxide (ITO) hole transport layer as in Example 1, and keeping the N2 glove box ready for use;
[0130] (2) Then, an active layer film was prepared on the hole transport layer by spin coating. The specific preparation process of different active layer solutions was as follows: the ratio of D18:L8-BO:AT-β2O(PX) was 1:1.2:0 and 1:1:0.2 (w / w), and the concentration of the donor when preparing active layers of different thicknesses was 8, 12.25, and 16.5 mg mL -1, then, the active layer solution was spin-coated on the PEDOT:PSS layer to obtain active layers with thicknesses of 100, 250, and 400 nm (the active layer did not require any post-treatment);
[0131] (3) Finally, in 1×10 -6 Under the condition of vacuum evaporation at 1000 mbar, C was deposited on the active layer in sequence. 60 (10nm) / BCP(5nm) / Ag(100nm) electrode. The active area of the device is 6.28mm 2 .
[0132] The performance of the above different organic solar cells was tested at AM 1.5G 100mW cm -2 The current-voltage curve is measured under illumination conditions, such as Fig.14 As shown, the corresponding battery performance parameters are obtained, see Table 10.
[0133] Table 10 Performance of OSCs of D18:L8-BO(PX) and D18:L8-BO:AT-β2O(PX) with different film thicknesses
[0134]
[0135]
[0136] At a film thickness of about 100nm, the PCE of the ternary cell is 17.68%, and the PCE of the binary cell with a similar film thickness is 16.22%. For both binary and ternary devices, when the active layer thickness increases from 100nm to 400nm, the maximum PCE of the binary device decreases from 16.22% to 10.78%, while the maximum PCE of the ternary device only decreases from 17.68% to 16.02%. Ternary devices are less sensitive to the thickness of the photoactive layer than binary devices, which is the key to maintaining high device PCE at thicker photoactive layer thicknesses.
[0137] Embodiment 8
[0138] An organic solar cell, the active layer material of which includes the above-mentioned non-fullerene acceptor, other Y series acceptors (DTY6) and donor materials (PM6), is prepared as follows:
[0139] (1) preparing an indium tin oxide (ITO) hole transport layer as in Example 1, and keeping the N2 glove box ready for use;
[0140] (2) Then, an active layer film was prepared on the hole transport layer by spin coating. The specific preparation process of different active layer solutions was as follows: the ratio of PM6:DTY6:AT-β2O(OX) was 1:1.2:0 and 1:1:0.2 (w / w), the additive was 0.5% CN, and the concentration of the donor when preparing active layers of different thicknesses was 8.2, 12.3, and 16.4 mg mL -1 , then the active layer solution was spin-coated on the PEDOT:PSS layer to obtain active layers with thicknesses of ∼100, 250, and 400 nm (the active layer did not require any post-treatment);
[0141] (3) Finally, in 1×10 -6 Under the condition of vacuum evaporation at 1000 mbar, C was deposited on the active layer in sequence. 60 (10nm) / BCP(5nm) / Ag(100nm) electrode. The active area of the device is 6.28mm 2 .
[0142] The performance of the above different organic solar cells was tested at AM 1.5G 100mW cm -2 The current-voltage curve is measured under illumination conditions, such as Fig.15 As shown, the corresponding battery performance parameters are obtained, see Table 11.
[0143] Table 11 Performance of OSCs of PM6:DTY6(OX) and PM6:DTY6:AT-β2O(OX) with different film thicknesses
[0144]
[0145]
[0146] Compared with binary OSCs, the PM6:DTY6:AT-β2O(OX) ternary devices show improved efficiencies of 1.18%, 3.07%, and 4.65% at 100nm, 250nm, and 400nm active layer thicknesses, respectively.
[0147] The present invention applies the receptor to OSCs treated with different solvents (chemical structures of relevant photovoltaic materials such as Fig. 9(shown) to examine the universality of spatially confined crystallized acceptors. When non-fullerene acceptors with spatially confined crystallization properties were added, the PCEs of all OSCs containing AT-β2O (halogenated solvents (CF) or non-halogenated solvents (toluene (TL), p-xylene (PX), and o-xylene (OX))) were significantly higher than those without AT-β2O, and the film thickness dependence was weak. OSCs with different solvent systems and active layer materials were prepared by various processing methods, such as spin coating and blade coating for D18-Cl:N3, solvent annealing for PM6:BTP-eC9 system, and thermal annealing for other active layers. These results collectively indicate that the proposed VSC strategy is universal and compatible with different active layers, solvents, processing methods, and post-treatment processes.
[0148] Embodiment 9
[0149] (1) The structure of large-area components is similar to that of small-area devices. 2 An OSC module with eight tandem subcells was fabricated on an ITO glass substrate with an opening area of 15.64 cm 2 The series interconnection of the components is achieved by P1, P2 and P3 lines (P1, P2, P3 are cut using the GH-LS300 laser cutting system). First, P1 is etched on the ITO with a laser, and the width of P1 is 30μm;
[0150] (2) PEDOT:PSS was then deposited, the active layer was scraped, C60 and BCP were deposited; before silver deposition, the P2 line was cut, and its width was about 140 μm;
[0151] (3) In 1×10 -6 The P3 (80 μm) line was formed by thermal evaporation of a 100 nm thick Ag electrode under a pressure of 100 mbar. At the same time, the edge was cleaned by laser; the distance between P1 and P2, and between P2 and P3 was 25 μm.
[0152] Test the above large area (PEDOT:PSS (35nm) / active layer (250nm) / C 60 (10nm) / BCP(5nm) / Ag(100nm), the effective area of the module is 15.03cm 2 ) Organic solar cell performance, and obtain the JV curve, such as Fig.16 As shown, the corresponding battery performance parameters are obtained according to the curve, see Table 12. Table 12 Photovoltaic performance parameters of OSC components based on chloroform processed D18-Cl:N3 and D18-Cl:N3:AT-β2O
[0153]
[0154]
[0155] a SIMIT certified efficiency in Shanghai, China.
[0156] High-quality thick active layers can suppress the formation of pinholes in the film, which is conducive to the rapid and large-scale production of efficient OSCs. 2 active layer. The 100nm active layer without spatially confined crystalline performance receptors exhibited randomly distributed pinholes. In contrast, the thick (~250nm) active layer exhibited a pinhole-free morphology with or without the addition of spatially confined crystalline performance receptor AT-β2O. Next, a module consisting of 8 sub-cells in series was prepared using the thick active layer under atmospheric conditions. Table 12 shows that the PCE of the device based on D18-Cl:N3:AT-β2O (1:1.2:0.2, 250nm) is 18.36% (certified as 18.04%), which is much higher than the PCE of the device based on D18-Cl:N3 (250nm) (10.26%). The significant difference in efficiency is mainly attributed to the different FF values (the FF of the component based on D18-Cl:N3 (250nm) is 56.63%, while the FF of the component based on D18-Cl:N3:AT-β2O (250nm) is 77.24%). The beam-induced current (LBIC) images generated by the 632nm laser scanning device show that the photocurrent of the D18-Cl:N3:AT-β2O (250nm) component is stronger and more uniformly distributed than that of the D18-Cl:N3 (250nm) component ( Fig.17 ). Currently, 18.36% are effective areas > 10cm 2 The highest efficiency of the OSC component far exceeds that of previous research reports, which proves that the receptor with spatially confined crystallization performance in the present invention can effectively improve the efficiency of the OSC component.
[0157] Comparative Example
[0158] Fig.18 It is the molecular formula of the comparative material BT-β2O in the comparative example.
[0159] An active layer material for an organic solar cell, taking N3:BT-β2O as an acceptor material and D18-Cl as a donor material as an example:
[0160] (1) preparing an indium tin oxide (ITO) hole transport layer as in Example 1, and keeping the N2 glove box ready for use;
[0161] (2) N3, D18-C, and BT-β2O were added to chloroform / diphenyl ether to prepare an active layer solution. The specific preparation process was as follows: the ratio of D18-Cl:N3:AT-β2O and D18-Cl:N3:BT-β2O was 1:1.2:0.2 (w / w, CF / DPE (volume ratio 96:4%), and the concentration of the donor was 5, 10, and 15 mg mL -1 Subsequently, the active layer solution was spin-coated on the PEDOT:PSS layer (without any post-treatment) to prepare active layers of different thicknesses.
[0162] (3) Finally, in 1×10 -6 Under the condition of vacuum evaporation at 1000 mbar, C was deposited on the active layer in sequence. 60 (10nm) / BCP(5nm) / Ag(100nm) electrode.
[0163] The active area of the device is 6.28mm 2 .
[0164] The performance of the above different organic solar cells was tested at AM 1.5G 100mW cm -2 The corresponding battery performance parameters are measured under irradiation conditions, see Table 13 and Fig.19 .
[0165] Table 13 Photovoltaic performance parameters of OSCs based on D18-Cl:N3:AT-β2O and D18-Cl:N3:BT-β2O with different thicknesses
[0166]
[0167] As shown in Table 13, the active layer D18-Cl: N3: BT-β2O ternary device developed based on the symmetrical OEG-substituted comparative material BT-β2O has a PCE of 19.27% when the active layer thickness is 100nm, which is lower than the efficiency of the D18-Cl: N3: AT-β2O ternary device (20.24%); when the film thickness reaches 400nm, the efficiency based on D18-Cl: N3: BT-β2O only maintains 15.87%, while the device based on D18-Cl: N3: AT-β2O maintains an efficiency of up to 17.93%. This trend shows that asymmetric OEG-substituted non-fullerene acceptors are essential for maintaining high photovoltaic performance in thick film devices.
[0168] The study shows that after the non-fullerene acceptor AT-β2O with spatially confined crystallization characteristics in the present invention is added to the main body (D18-Cl:N3 system), it can utilize the molecular interaction between itself and N3 to regulate the assembly behavior of N3. The regulation of N3 nucleation and molecular assembly by AT-β2O can enhance and well maintain the crystallinity of N3:AT-β2O thin film. At the same time, the addition of AT-β2O can optimize the vertical phase separation of the thick film active layer, which in turn helps to obtain a more balanced charge transfer, greatly improving the energy conversion efficiency of the thick film device. In addition, the universality of the acceptor with spatially confined crystallization characteristics has been confirmed in different active layer systems, processing solvents, preparation and post-treatment processes.
[0169] The non-fullerene acceptor with spatially confined crystallization characteristics disclosed in the present invention is added as a guest molecule to the main component, which solves the problems of pinholes and low performance of thick-film devices caused by low film thickness in large-area components, and ultimately obtains a large-area device module with high performance and high stability, thereby promoting the industrialization of organic solar cells.
Claims
1. A non-fullerene receptor with spatially confined crystallization, characterized in that: The non-fullerene acceptor with spatially confined crystallization contains an ethylene glycol group; the chemical structural formula of the non-fullerene acceptor with spatially confined crystallization is one of the following chemical structural formulas: ; Wherein, X1, X2, X3, and X4 are independently selected from one of O, S, Se, and Te; D1 to D4 are independently selected from one of H, CH3, OCH3, F, Cl, Br, CF3, CN, and C a H 2a+1 One of the following, wherein a is 1 to 20; The end groups A1 and A2 are independently selected from one of the following structural formulas: ; Wherein B1 and B2 are independently selected from or ; B3-B8 are independently selected from H, CH3, OCH3, F, Cl, Br, CF3, CN, C b H 2b+1 One of the following, wherein b is 1 to 20; R1 is -C n H 2n+1 , wherein n is 1 to 20; R2 is -(CH2CH2O) m CH3 or -C n H 2n+1 , wherein m is 1 to 10, n is 1 to 20; R3 is -(CH2CH2O) m CH3 or -C n H 2n+1 , wherein m is 1 to 10, n is 1 to 20; R4 is hydrogen, -(CH2CH2O) m CH3 or -C n H 2n+1 , wherein m is 1 to 10, n is 1 to 20; R5 is hydrogen, -(CH2CH2O) m CH3 or -C n H 2n+1 , where m is 1 to 10, n is 1 to 20; In Formula 1, Formula 4, Formula 5, and Formula 6, R2 is different from R3; in Formula 2, R2, R3, and R4 are not completely the same; in Formula 3, R2, R3, R4, and R5 are not completely the same.
2. The non-fullerene acceptor with spatially confined crystals according to claim 1, characterized in that: R1 is -C n H 2n+1 , wherein n is 3 to 10; R2 is -(CH2CH2O) m CH3 or -C n H 2n+1 , wherein m is 1 to 5, n is 5 to 15; R3 is -(CH2CH2O) m CH3 or -C n H 2n+1 , wherein m is 1 to 5, n is 5 to 15; R4 is hydrogen or -C n H 2n+1 , wherein n is 3 to 15; R5 is hydrogen or -C n H 2n+1 , where n is 3 to 15.
3. Use of the non-fullerene acceptor with spatially confined crystallization according to claim 1 in the preparation of an organic solar cell or an active layer of an organic solar cell.
4. The method for preparing a non-fullerene receptor with spatially confined crystallization according to claim 1, characterized in that: The method comprises the following steps: reacting a DA'D type conjugated core with an electron-withdrawing end group to obtain a non-fullerene acceptor with spatially confined crystals.
5. The method for preparing a non-fullerene receptor with spatially confined crystallization according to claim 4, characterized in that: The reaction is carried out in the presence of an organic catalyst.
6. Use of the non-fullerene acceptor with spatially confined crystallization properties as claimed in claim 1 in improving the efficiency of ultra-thick active layer solar cells.
7. An active layer material for an organic solar cell, characterized in that: It includes the non-fullerene acceptor with spatially confined crystallization performance as described in claim 1.
8. The active layer material for an organic solar cell according to claim 7, characterized in that: It also includes Y series receptor and donor materials.
9. An organic solar cell comprising an active layer, an electron transport layer, a hole transport layer and an electrode, characterized in that: The active layer includes the non-fullerene acceptor with spatially confined crystallization properties as claimed in claim 1.
10. A method for preparing an organic solar cell, comprising the following steps: sequentially preparing a hole transport layer, an active layer, an electron transport layer and an electrode on a conductive substrate to obtain an organic solar cell; characterized in that: The active layer includes the non-fullerene acceptor with spatially confined crystallization properties as claimed in claim 1.
Citation Information
Patent Citations
Ternary organic solar cell structure based on micromolecule non-fullerene receptor, and preparation method for ternary organic solar cell structure
CN108550699A
Application of phenol-substituted fullerene derivative in perovskite solar cell, perovskite solar cell and preparation method of perovskite solar cell
CN109742245A
Non-fullerene receptor with collaborative assembly characteristic as well as preparation method and application of non-fullerene receptor
CN113880862A